Testosterone level in angiographically detected coronary artery disease and myocardial infarction - Rahman, Lajan Qasim; Yousf, Salah Hassan; Al Barzinj, Ruqaya Muhammed (Diyala Journal of Medicine, 2019)
Background: Coronary artery disease a dominant cause for morbidity and mortality. Risk factors in the form of clinical data or biomarkers for atherosclerosis are useful for risk stratification, treatment and prevention. Objective: This study aims to assess the level of testosterone in stable atherosclerotic heart disease and myocardial infarction compared to normal and effect of DM on testosterone in ischemic heart disease in both stable ischemia and myocardial infarction. Patients and Methods: In this cross sectional study a total number of 65 male patients were taken. 35 patients with angiographically detected atherosclerosis and 30 patients admitted with acute myocardial infarction that compared to 30 normal controls in Hawler cardiac center during the period from 8th September 2014 till 2nd February 2015. Results: The level of testosterone was 0.470 ± 0.655ng/ml in atherosclerotic coronary arteries, 0.043 ± 0.008ng/ml in patients with history of acute myocardial infarction and 1.12 ± 0.29 ng/ml in healthy control male, which was statistically significant (P-value 0.002), diabetic patient had further lower testosterone level in all group. Conclusion: Testosterone assessment may be beneficial in patients with recognized coronary artery disease with no significant conventional risk factors and it could be a novel risk factor if larger studies performed assessing testosterone level in atherosclerosis.